Oligoether-Substituted Derivatives of Carbon-Rich 1,4,7,10,13,16-Hexaethynyltribenzo[a,e,i]cyclododeca-5,11,17-triyne (C36H12) and 1,4,9,12-Tetrakis(ethynyl)dibenzo[a,g]cyclododeca-5,7,13,15-tetrayne (C28H8): Potential Precursors to the Circular [6]Phenylene (‘Antikekulene’) Frame - Dahlmann, Uwe; Vollhardt, K. Peter C. (Synthesis, 2020)
The title compounds, in which the terminal alkyne functions are adorned with -CH2OCH2CH2OCH2CH2OCH2CH3 or -p-C6H4OCH2CH2 OCH2CH2OCH3 substituents, were synthesized. The strategies for their preparation relied on prior art and involved the use of Sonogashira alkynylations of appropriate haloarenes, Stephens–Castro cyclizations of 1,2,4-trialkynyl-3-iodobenzenes, and Hay oxidative couplings of 1,2,3,4-tetralkynylbenzenes. The targets form yellow materials, exhibiting yellow-green fluorescence, and they are very soluble in polar solvents, but only sparingly so in nonpolar media. Attempts to convert them into the antikekulene frame through CpCo(CO)2-catalyzed (co)-cyclizations failed.
Keywords: alkynes; carbon-rich compounds; cyclotrimerizations; dehydroannulenes; phenylenes